2018
DOI: 10.1016/j.cub.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Size Laws and Division Ring Dynamics in Filamentous Escherichia coli cells

Abstract: Our understanding of bacterial cell size control is based mainly on stress-free growth conditions in the laboratory [1-10]. In the real world, however, bacteria are routinely faced with stresses that produce long filamentous cell morphologies [11-28]. Escherichia coli is observed to filament in response to DNA damage [22-25], antibiotic treatment [11-14, 28], host immune systems [15, 16], temperature [17], starvation [20], and more [18, 19, 21], conditions which are relevant to clinical settings and food prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 61 publications
16
107
0
Order By: Relevance
“…The numerical results for the backward distribution ψ bw shown in Figure 1B are qualitatively very similar to the tree distribution obtained via Equation (15) and also to the lineage distribution computed by solving Equation (4).…”
Section: Comparison Of Cell Size Distributionssupporting
confidence: 68%
See 2 more Smart Citations
“…The numerical results for the backward distribution ψ bw shown in Figure 1B are qualitatively very similar to the tree distribution obtained via Equation (15) and also to the lineage distribution computed by solving Equation (4).…”
Section: Comparison Of Cell Size Distributionssupporting
confidence: 68%
“…We hence expect our conclusions to hold also for developed models of cell size control. We found that these differences are particularly sensitive to division errors, which can be extremely heterogeneous when cells respond to stress [4]. Conversely, we found that cells dividing at smaller sizes are over-represented in the population tree when division size is highly variable.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, recently it was shown that in artificially generated filamentous E. coli cells the Z‐ring reorganize to form one cell length (the length of a non‐elongated cell) away from the cell pole and regularly at a distance of two length‐units away from each other along the cell length. Interestingly, these localization patterns of the Z‐ring could be attributed to the localization dynamics of the Min‐system (Wehrens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Wehrens and Ershove et al recently published highly complementary findings in E. coli cells that were elongated due to stress (Wehrens et al, ). In these growing filamentous cells, multiple Fts rings were evenly distributed in response to the multi‐nodal dynamics of the Min system.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 97%